2012
DOI: 10.1136/archdischild-2011-300685
|View full text |Cite
|
Sign up to set email alerts
|

Puberty is associated with increased deterioration of renal function in patients with CKD: data from the ItalKid Project

Abstract: The present analysis suggests that puberty is associated with increased deterioration of renal function in CKD. The mechanism(s) underlying this unique and specific (to children) pattern of progression have not yet been identified, but it may be that sex hormones play a role in this puberty-related progression of CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 26 publications
1
32
0
1
Order By: Relevance
“…Analysis of the paired differences in percent GFR decline showed no significant differences between the subjects with ARPKD and either control group (data not shown). Because baseline GFR and puberty/older age have been associated with more rapid decline in renal function, 18,19 we performed subanalyses to examine the impact of these two factors on GFR decline. Subjects with ARPKD and control subjects were stratified into two baseline GFR groups: GFR <45 or ≥45 ml/min/1.73m 2 and two age groups: <10 vs. ≥10 years of age.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the paired differences in percent GFR decline showed no significant differences between the subjects with ARPKD and either control group (data not shown). Because baseline GFR and puberty/older age have been associated with more rapid decline in renal function, 18,19 we performed subanalyses to examine the impact of these two factors on GFR decline. Subjects with ARPKD and control subjects were stratified into two baseline GFR groups: GFR <45 or ≥45 ml/min/1.73m 2 and two age groups: <10 vs. ≥10 years of age.…”
Section: Resultsmentioning
confidence: 99%
“…Data from the ItalKid Project [32] showed that the probability of RRT was 9.4% during the first decade of life and 51.8% during the second decade. There was a clear break point at puberty in the kidney survival curve, with an ensuing decline after puberty in both males and females.…”
Section: Factors Affecting Progression Of Ckdmentioning
confidence: 99%
“…Loss of renal function with progression through adolescence is well demonstrated and not solely explained by noncompliance of teenagers. The ItalKid study authors suggested that the possible mechanisms for this fi nding are: (1) imbalance between glomerular capacity and increased body mass, or (2) an effect related to the changing sex hormone environment with progression [ 47 ]. In addition, adolescence and young adulthood also represent a time of sexual growth and experimentation, and for young men with PUV, erectile dysfunction, ejaculatory issues, and fertility are of paramount concern.…”
Section: Follow-upmentioning
confidence: 97%